2011
DOI: 10.1021/jf2012584
|View full text |Cite
|
Sign up to set email alerts
|

Growth Suppression of HER2-Overexpressing Breast Cancer Cells by Berberine via Modulation of the HER2/PI3K/Akt Signaling Pathway

Abstract: Berberine (BBR) is a natural alkaloid with significant antitumor activities against many types of cancer cells. This study investigated the molecular mechanisms by which BBR suppresses the growth of HER2-overexpressing breast cancer cells. The results show that BBR induces G1-phase cell cycle arrest by interfering with the expression of cyclins D1 and E and that it induces cellular apoptosis through the induction of a mitochondria/caspase pathway. The data also indicate that BBR inhibits cellular growth and pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
52
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 71 publications
(54 citation statements)
references
References 35 publications
2
52
0
Order By: Relevance
“…35) Suppression of the EGFR signaling pathway by berberine has been reported by several groups. 31,36,37) Berberine inhibited growth and promoted apoptosis of breast cancer cells 38) and the mechanism was shown to be via inhibition of the HER2 signaling pathway. This evidence suggests the inhibition of ERK upstream stimuli, EGFR and HER2 being the mechanism by which berberine affected the ERK pathway as observed in the current study.…”
Section: )mentioning
confidence: 99%
“…35) Suppression of the EGFR signaling pathway by berberine has been reported by several groups. 31,36,37) Berberine inhibited growth and promoted apoptosis of breast cancer cells 38) and the mechanism was shown to be via inhibition of the HER2 signaling pathway. This evidence suggests the inhibition of ERK upstream stimuli, EGFR and HER2 being the mechanism by which berberine affected the ERK pathway as observed in the current study.…”
Section: )mentioning
confidence: 99%
“…BBR has multiple pharmacological properties including antioxidant, anti-apoptotic, and anticancer effects and activity against obesity and Alzheimer’s disease [13-16]. BBR affects cancer cell proliferation with consequent impairment of cell division through downregulation of cyclin B1 and upregulation of p21 in a variety of cancer types, including lung and breast cancer cells [17-19].…”
Section: Introductionmentioning
confidence: 99%
“…BBR affects cancer cell proliferation with consequent impairment of cell division through downregulation of cyclin B1 and upregulation of p21 in a variety of cancer types, including lung and breast cancer cells [17-19]. In addition, BBR triggers pro-apoptotic effects through suppression of the HER2/PI3K/AKT signaling pathway [16]. We also reported that inhibition of AP-1 transcriptional activity by BBR treatment suppresses invasion of breast cancer cells [20].…”
Section: Introductionmentioning
confidence: 99%
“…Induction of apoptosis of cancer cells, mainly through the mitochondrial-and death receptor-dependent pathways, is the principal strategy for chemotherapy. In addition, several other pathways involved in cell apoptosis are influenced by chemotherapeutic drugs (31)(32)(33). Berberine has been demonstrated to induce apoptosis of cancer cells including SW60 and HepG2 cells by interfering with the expression of molecules in pathways including Bcl-2, Bax and caspase-3 (34)(35)(36).…”
Section: Introductionmentioning
confidence: 99%